2005
DOI: 10.1111/j.0014-3820.2005.tb01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Speciation in the Cosmopolitan and Clonal Human Pathogenic Fungus Aspergillus Fumigatus

Abstract: Abstract. Microbes and other organisms smaller than one to a few millimeters in size are hypothesized to have global populations, in contrast to the geographically restricted ranges of larger organisms. However, fungi, which routinely have reproductive propagules no larger than 10 micrometers, challenge the generality of this hypothesis because recent studies have shown that globally distributed morphological species embrace two or more geographically restricted phylogenetic species. We used the concordance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(123 citation statements)
references
References 109 publications
7
114
2
Order By: Relevance
“…A previous study by Rydholm et al [70], analysing the genetic structure of A. fumigatus, suggested that A. fumigatus is cosmopolitan and randomly breeding across a global scale. A subsequent study, while confirming these aspects of the population genetic structure of A. fumigatus, also found evidence of a genetic barrier to gene flow, suggesting A. fumigatus contained two (or perhaps more) cryptic and morphologically identical species [68]. More recent studies have confirmed the occurrence of a separate sexual species, A. lentulus [71] and have hinted at the existence of further genetic diversity within A. fumigatus sensu stricto.…”
Section: Population Structure Of Azole-resistant Aspergillus Fumigatusmentioning
confidence: 68%
See 2 more Smart Citations
“…A previous study by Rydholm et al [70], analysing the genetic structure of A. fumigatus, suggested that A. fumigatus is cosmopolitan and randomly breeding across a global scale. A subsequent study, while confirming these aspects of the population genetic structure of A. fumigatus, also found evidence of a genetic barrier to gene flow, suggesting A. fumigatus contained two (or perhaps more) cryptic and morphologically identical species [68]. More recent studies have confirmed the occurrence of a separate sexual species, A. lentulus [71] and have hinted at the existence of further genetic diversity within A. fumigatus sensu stricto.…”
Section: Population Structure Of Azole-resistant Aspergillus Fumigatusmentioning
confidence: 68%
“…This cluster also contained three UK isolates, one isolate from The Netherlands, and only 1/20 isolates carrying the TR 34 /L98H allele compared with 15/20 for the non-Japanese clade (figure 2). This preliminary population genomics analysis suggests that Pringle et al [68] are correct and that cryptic and morphologically identical populations of A. fumigatus sensu stricto do occur, and that this genetic structure leads to substantial linkage disequilibrium for at least two important genetic markers, the mating types and azole-resistance alleles.…”
Section: Population Structure Of Azole-resistant Aspergillus Fumigatusmentioning
confidence: 74%
See 1 more Smart Citation
“…2C; Leavitt et al 2011a;Leavitt et al 2013). Additionally, genealogical concordance among independent genetic markers can provide strong evidence that distinct clades represent reproductively isolated lineages among well-separated groups (Dettman et al 2003;Pringle et al 2005). Although different datasets and operational criteria may give conflicting or ambiguous results due to the multiple evolutionary processes associated with speciation, the use of multilocus sequence data and multiple empirical methods are known to establish robust species boundaries in many lichen-forming fungal lineages (reviewed in Lumbsch and Leavitt 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the same strongly supported monophyletic clades -'A' and 'C' -were recovered in reciprocally monophyletic clades in the independent gene trees (data not shown) (Hudson and Coyne 2002). Presence of the same clades in different single-locus genealogies can be taken as strong evidence that the clades are reproductively and evolutionarily isolated lineages representing distinct species-level lineages (Dettman et al 2003;Pringle et al 2005;de Quieroz 2007). The relationships among the clades were well supported (Fig.…”
Section: Resultsmentioning
confidence: 71%